How Servant Leadership Affects Job Satisfaction and Organizational Commitment in the post COVID-19 era - Bevanda, Nevena; Bevanda, Vuk; Pavlović, Goran (Anali Ekonomskog fakulteta u Subotici, 2025)
This study aims to investigate how servant leadership influences job satisfaction and organizational commitment in the post-COVID-19 era. Its objective is to understand how servant leadership, with its focus on empathy and employee well-being, has influenced these key organizational outcomes following the challenges brought by the pandemic. Primary data were collected using a survey method, and descriptive statistics, correlation, and simple regression were employed to analyze the data. The data collection took place in September 2024, with a sample of 101 respondents. The main requirement for the sample was that respondents work in an organization located in Serbia. The results show that servant leadership significantly influences both job satisfaction and organizational commitment. Given that job satisfaction, employee commitment, and retention significantly influence organizational efficiency, effectiveness, and performance, it is essential for top management to continuously monitor these indicators. Based on the results, organizations should implement specific measures to mitigate negative influences and further enhance the positive effects of servant leadership.